Comparison of closely related, uncultivated Coxiella tick endosymbiont population genomes reveals clues about the mechanisms of symbiosis. (26th April 2018) - Tsementzi, Despina; Castro Gordillo, Juan; Mahagna, Mustafa; Gottlieb, Yuval; Konstantinidis, Konstantinos T.
Summary: Understanding the symbiotic interaction between Coxiella ‐like endosymbionts (CLE) and their tick hosts is challenging due to lack of isolates and difficulties in tick functional assays. Here we sequenced the metagenome of a CLE population from wild Rhipicephalus sanguineus ticks (CRs) and compared it to the previously published genome of its close relative, CLE of R. turanicus (CRt). The tick hosts are closely related sympatric species, and their two endosymbiont genomes are highly similar with only minor differences in gene content. Both genomes encode numerous pseudogenes, consistent with an ongoing genome reduction process. In silico flux balance metabolic analysis (FBA) revealed the excess production of L‐proline for both genomes, indicating a possible proline transport from Coxiella to the tick. Additionally, both CR genomes encode multiple copies of the proline/betaine transporter, proP gene. Modelling additional Coxiellaceae members including other tick CLE, did not identify proline as an excreted metabolite. Although both CRs and CRt genomes encode intact B vitamin synthesis pathway genes, which are presumed to underlay the mechanism of CLE‐tick symbiosis, the FBA analysis indicated no changes for their products. Therefore, this study provides new testable hypotheses for the symbiosis mechanism and a better understanding of CLE genome evolution and diversity.